Rapid Synthesis and Sintering of Nanostructured MgTiO3 Compound by High-Frequency Induction Heating - Kang, Hyun-Su; Doh, Jung-Mann; Yoon, Jin-Kook; Park, Bang-Ju; Shon, In-Jin (KOREAN INST METALS MATERIALS, 2012)
Nanopowders of MgO and TiO2 were made by high energy ball milling. The rapid synthesis and sintering of the nanostructured MgTiO3 compound was investigated by the high-frequency induction heated sintering process. The advantage of this process is that it allows very quick densification to near theoretical density and inhibition grain growth. Nanocrystalline materials have received much attention as advanced engineering materials with improved physical and mechanical properties. As nanomaterials possess high strength, high hardness, excellent ductility and toughness, undoubtedly, more attention has been paid for the application of nanomaterials. A highly dense nanostructured MgTiO3 compound was produced with simultaneous application of 80 MPa pressure and induced current within 2 min. The sintering behavior, gain size and mechanical properties of MgTiO3 compound were investigated.